2005
DOI: 10.1063/1.1938191
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between lysozyme and glycerol dynamics: Microscopic insights from molecular-dynamics simulations

Abstract: We explore possible molecular mechanisms behind the coupling of protein and solvent dynamics using atomistic molecular-dynamics simulations. For this purpose, we analyze the model protein lysozyme in glycerol, a well-known protein-preserving agent. We find that the dynamics of the hydrogen bond network between the solvent molecules in the first shell and the surface residues of the protein controls the structural relaxation (dynamics) of the whole protein. Specifically, we find a power-law relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 53 publications
(64 reference statements)
7
72
0
Order By: Relevance
“…This has been shown to be true in ref. [19] for the case of Ribonuclease A in pure water and by Dirama et al [57] for the case of Lysozyme in glycerol or in trehalose [18]. Thus, the effect of an increase in trehalose concentration is very similar to that of a decrease in temperature.…”
Section: H(t)supporting
confidence: 53%
See 1 more Smart Citation
“…This has been shown to be true in ref. [19] for the case of Ribonuclease A in pure water and by Dirama et al [57] for the case of Lysozyme in glycerol or in trehalose [18]. Thus, the effect of an increase in trehalose concentration is very similar to that of a decrease in temperature.…”
Section: H(t)supporting
confidence: 53%
“…The behavior of proteins in pure water [19, and pure trehalose [18,57] has been studied extensively using computer simulation methods. In the particular case of globular proteins immersed in trehalose-water binary mixtures Lins et al [58] and Lebret et al [56] have reported studies of Lysozyme in various trehalose-water mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…No dependence on NADPH concentration was observed although we noted that in these laser photoexcitation experiments the initial concentration of NADPH was relatively high to ensure that prior to catalysis all of the Pchlide substrate was in the ternary substrate complex form. As the enzyme also has a high affinity for NADPH (18,19) it is perhaps not surprising that a dependence on the NADPH concentration is not observed.…”
Section: Figure 4 the Effects Of Nadpmentioning
confidence: 99%
“…[14] Most neutron and MD studies to date have investigated the MSD on a picosecond-nanosecond (ps-ns) timescale. [1,5,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] At low temperatures (T < 100 K), a protein is essentially harmonic. As the temperature is increased beyond the harmonic regime, proline puckering transitions and methyl rotations are activated.…”
Section: Introductionmentioning
confidence: 99%
“…Similar simulation systems are discussed in the literature. [8,26,[41][42][43][44] The system was simulated using GROMACS 4.5.1.…”
Section: Introductionmentioning
confidence: 99%